26. PERAN UNICEF DALAM MENANGANI KASUS ABORSI DAN PERDAGANGAN ANAK DI TIONGKOK TAHUN 2008-2014 - Maharani Alvionita Richie Mediana; Reni Windiani; Satwika Paramasatya (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
One child policy has been implemented by the China’s government since 1979. This policycaused, abortion and child trafficking that have been increased in 2008-2014. Asinternational organization focusing on child’s life quality, UNICEF (United Nations ofChildren’s Fund) plays role to deal with abortion and child trafficking in China. Thisresearch used descriptive approach through secondary data using international organizationconcept. This research described the role of UNICEF in dealing with abortion and childtrafficking in China 2008-2014. The result of this study indicated that UNICEF played aneffective reducing role in abortion and child trafficking through health care and protectionfor both mother and children, as well as carried out programs for realizing the rights ofchildren.